A foldable underwater acoustic meta-structure with broadband sound absorption at low frequency. (1st June 2022) - Ke, Yibo; Li, Zhaoyu; Wu, Guanghua; Zhang, Lin; Tao, Meng
Abstract: An underwater absorber consisting of a microperforated panel, foldable channel and rubber coating with perfect low-frequency sound absorption, broadband absorption and strong resistance to deformation is presented. The theoretical prediction and simulation analysis are in good agreement. It is demonstrated that sound energy is mainly dissipated in the rubber coating due to waveform conversion at the coupling boundary. A meta -structure with low-frequency and broadband absorption is realized by optimizing the structural parameters. Moreover, at a relatively regulated low-frequency wavelength, the spatial folded structure enables a deep subwavelength dimension. The proposed meta -structure has wide potential applications in underwater noise control.